QUALITY OF LIFE: THE SPIRITUALITY AND SPIRITUAL WELLBEING OF ELDERLIES IN MALAYSIA - Yahya, Fatimah Binti; Hassan, Hafizah Che; Panduragan, Santhna Letchmi; Mat, Samsiah (LPPM Universitas Jambi, 2024)
With an increasing aging population worldwide, there is a need for greater focus on the spirituality of older people, to better support them and lead them to an enhancement of their inner peace. This study used a qualitative with exploratory sequential design approach (with semi-structured interviews) in exploring spirituality with older people in community of Federal Territory of Kuala Lumpur, which is related to a sense of personal belief and connection that helped them in their daily lives. The research involved a rigorous exploratory process. The fifteen (15) participants provided information about their rich experiences and their connections in four domains: (1) Faith, (2) Belief, (3) Practice and (4) Emotion. Results: The reliability of the dimensions was all high as the Cronbach’s Alpha coefficients were above 0.90. Therefore, this spirituality measurement tool can be considered highly reliable. Conclusion: This paper has developed as well as validate the spirituality measurement tool. It was used to construct a profile of elderly in Malaysia, and it may be applied to profile elderly in other countries.